Faecal DNA to the rescue: Shotgun sequencing of non-invasive samples reveals two subspecies of Southeast Asian primates to be Critically Endangered species - Ang, Andie (Sci Rep, 2020)
A significant number of Southeast Asian mammal species described in the 19(th) and 20(th) century were subsequently synonymized and are now considered subspecies. Many are affected by rapid habitat loss which creates an urgent need to re-assess the conservation status based on species boundaries established with molecular data. However, such data are lacking and difficult to obtain for many populations and subspecies. We document via a literature survey and empirical study how shotgun sequencing of faecal DNA is a still underutilized but powerful tool for accelerating such evaluations. We obtain 11 mitochondrial genomes for three subspecies in the langur genus Presbytis through shotgun sequencing of faecal DNA (P. femoralis femoralis, P. f. percura, P. siamensis cf. cana). The genomes support the resurrection of all three subspecies to species based on multiple species delimitation algorithms (PTP, ABGD, Objective Clustering) applied to a dataset covering 40 species and 43 subspecies of Asian colobines. For two of the newly recognized species (P. femoralis, P. percura), the results lead to an immediate change in IUCN status to Critically Endangered due to small population sizes and fragmented habitats. We conclude that faecal DNA should be more widely used for clarifying species boundaries in endangered mammals.